Ukrainian steel and ferroalloys in 2022-2024: how russian aggression has impacted on the work of the country's metallurgical industry - Gryshchenko , S.G.; Proidak , Yu.S.; Ponomarennko , R.V.; Kravchenko , A.P.; Kalenkov , O.F.; Kudriavtsev , S.L. (Theory and Practice of Metallurgy, 2025)
This article analyzes the state of the Ukrainian metallurgical industry, particularly steel and ferroalloy production, between 2022 and 2024, emphasizing the significant impact of the full-scale russian aggression. It highlights the industry's successes in 2021, when growth in steel and ferroalloy production was driven by favorable market conditions. The consequences of the russian invasion are detailed, including territorial occupation, infrastructure destruction, challenges with logistics and raw materials, and a shortage of qualified personnel, which led to a threefold reduction in steel production in 2022 and a substantial decline in ferroalloy output. Statistical data for 2022-2024 is presented, showing a gradual recovery in steel production volumes and a continued decrease in ferroalloy production, even leading to plant shutdowns in the fourth quarter of 2023. Special attention is given to the measures undertaken by Ukrainian enterprises to adapt to the new circumstances, including reorienting towards alternative raw material sources and optimizing electrotechnological regimes. The systemic problems facing the industry are highlighted: proximity to conflict zones, high electricity tariffs, personnel shortages, and logistical difficulties. In the context of Ukraine's European integration and its commitment to "green metallurgy," the prospects for the recovery and development of the domestic metallurgical sector are discussed, including projects for direct reduced iron and "green" steel production. Ukraine's potential to become a key supplier of "green" metallurgical raw materials for Europe is underscored.